Развитие культуры чтения как одна из основных задач в процессе обучения русскому языку студентов неязыковых групп - Амбарцумян, И. Г.
Speech activity both in the mother tongue and foreign language can not be perfect without reading habits. Consequently, from the point of view author, teaching reading as one of the kinds of speech activity is the most important educational problem, which must be solved by the Russian language teacher during practical classes, as the reading culture is the necessary basis for further improvement of students's quality of teaching.
Keywords: Методика преподавания русского языка